Key Factors in Decision Making for ECLS: A Binational Factorial Survey. (April 2022) - Drewniak, Daniel; Brandi, Giovanna; Buehler, Philipp Karl; Steiger, Peter; Hagenbuch, Niels; Stamm-Balderjahn, Sabine; Schenk, Liane; Rosca, Ana; Krones, Tanja
Background: Extracorporeal life support (ECLS) provides support to patients with cardiopulmonary failure refractory to conventional therapy. While ECLS is potentially life-saving, it is associated with severe complications; decision making to initiate ECLS must, therefore, carefully consider which patients ECLS potentially benefits despite its consequences. Objective: To answer 2 questions: First, which medically relevant patient factors influence decisions to initiate ECLS? Second, what are factors relevant to decisions to withdraw a running ECLS treatment? Methods: We conducted a factorial survey among 420 physicians from 111 hospitals in Switzerland and Germany. The study included 2 scenarios: 1 explored willingness to initiate ECLS, and 1 explored willingness to withdraw a running ECLS treatment. Each participant responded to 5 different vignettes for each scenario. Vignettes were analyzed using mixed-effects regression models with random intercepts. Results: Factors in the vignettes such as patients' age, treatment costs, therapeutic goal, comorbidities, and neurological outcome significantly influenced the decision to initiate ECLS. When it came to the decision to withdraw ECLS, patients' age, days on ECLS, criteria for discontinuation, condition of the patient, comorbidities, and neurological outcome were significant factors. In both scenarios, patients' age and neurological outcome were the most influential factors. Conclusions: This study provided insights into physicians' decision making processes about ECLS initiation and withdrawal. Patients' age and neurological status were the strongest factors influencing decisions regarding initiation of ECLS as well as for ECLS withdrawal. The findings may contribute to a more refined understanding of complex decision making for ECLS.